INJUSTICE IN RIDLEY SCOTT'S GLADIATOR MOVIE: A MARXIST APPROACH - Amrulloh, Okfani (2010)
The major problem of this study is injustice is faced by Maximus reflected in Gladiator movie. The objective of this study is to expose injustice faced by Maximus based on the Marxist approach by Karl Marx. The benefits of the study are To give some contributions to the larger body of knowledge particularly studies in Ridley Scott's Gladiator. The study belongs to the qualitative study. The object of the study is the movie of Ridley Scott Gladiator . Released in the United States on May 5, 2000. The primary data source is the main data obtained from the movie script which form such like the scene of the movie itself and the texts which form such like words, phrases, and sentences in dialogues or monologues occurring in the movie related to the topic and the secondary data sources are the supporting data taken from literary books, criticism, and some articles related to the movie. The method of data collection is library research by note-taking for the texts. The technique of data analysis used in this study is descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis, it is apparent that in this movie Ridley Scott conveys a moral message that every person is same in the eyes of God, just their morality that distinguish them. Second, based on the Marxist analysis, it is evident that in this movie, Ridley wants to rebel the social relation and stratification to get same rights.